Effective Strategies In Learning Media Development In The Digital Era - Novina Anjalina Nur Anisa; Donna Boedi Maritasari; Eli Yusfiana; Hizbul Wathan Zikri (Generasi Sains Indonesia, 2025)
Digital-based learning media has become an essential component of contemporary education, driven by the acceleration of technological transformation. This study aims to synthesize effective strategies in the development of digital learning media through a systematic literature review. Findings from the analysis reveal five key strategies: Conducting student needs analysis, Applying instructional design models such as ADDIE, Utilizing digital technology and interactive platforms, Integrating continuous evaluation and revision, and Strengthening teacher competence through TPACK-based professional development. These strategies are contextualized within broader challenges, including limited infrastructure, uneven digital literacy, and resistance to change among educators. The study highlights that effective strategies must be integrative, context-sensitive, and iterative. This review contributes to academic discourse by aligning practical strategies with theoretical models and by identifying research gaps for future studies in educational technology.